2015
DOI: 10.1089/pop.2014.0084
|View full text |Cite
|
Sign up to set email alerts
|

Is Diabetes Color-Blind? Growth of Prevalence of Diagnosed Diabetes in Children Through 2030

Abstract: Diabetes knows no age and affects millions of individuals. Preventing diabetes in children is increasingly becoming a major health policy concern and focus. The objective of this study is to project the number of children, aged 0-17 years, with diagnosed diabetes in the United States through 2030, accounting for changing demography, and diabetes and obesity prevalence rates. The study team combined historic diabetes and obesity prevalence data with US child population estimates and projections. A times-series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…According to the CDC, Hispanics have a 130% greater prevalence of diabetes than non-Hispanic whites [ 93 ]. Understanding these discrepancies is crucial, given the expansion of the Hispanic population and the rise in the frequency and incidence of T1DM among Hispanic children [ 94 , 95 , 96 ]. Although there is more material on the distinct healthcare experiences of the Hispanic community, few qualitative studies have reported on Hispanic kids with T1DM [ 96 ].…”
Section: Caregiving In Diabetesmentioning
confidence: 99%
“…According to the CDC, Hispanics have a 130% greater prevalence of diabetes than non-Hispanic whites [ 93 ]. Understanding these discrepancies is crucial, given the expansion of the Hispanic population and the rise in the frequency and incidence of T1DM among Hispanic children [ 94 , 95 , 96 ]. Although there is more material on the distinct healthcare experiences of the Hispanic community, few qualitative studies have reported on Hispanic kids with T1DM [ 96 ].…”
Section: Caregiving In Diabetesmentioning
confidence: 99%
“…Given the growth in the Hispanic community and the increase in prevalence and incidence in T1D among Hispanic youth, it is essential to understand these disparities 4,15–17 . While the literature has grown regarding the unique experience of healthcare among the Hispanic population, qualitative studies in Hispanic youth with T1D are limited 4,15 .…”
Section: Introductionmentioning
confidence: 99%
“…3,[10][11][12][13][14] Given the growth in the Hispanic community and the increase in prevalence and incidence in T1D among Hispanic youth, it is essential to understand these disparities. 4,[15][16][17] While the literature has grown regarding the unique experience of healthcare among the Hispanic population, qualitative studies in Hispanic youth with T1D are limited. 4,15 Existing literature points to the unique features of Hispanic caregiver stress in pediatric chronic diseases such as asthma and cancer including struggles to incorporate traditional beliefs, access culturally appropriate education, and involve the extended family in the care support structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is a chronic disease resulting from a relative or absolute deficiency of insulin, which affects the metabolism of carbohydrate, protein and fat [1]. Commonly occurring complications are nephropathy, dyslipidaemia, neuropathy, and retinopathy [2]. Sardinia (Italy) together with Finland and Sweden are known to have the highest incidence of type 1 diabetes in the world [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%